Alcohol‐induced respiratory symptoms improve after aspirin desensitization in patients with aspirin‐exacerbated respiratory disease. Issue 10 (10th July 2018) - Glicksman, Jordan T.; Parasher, Arjun K.; Doghramji, Laurel; Brauer, David; Waldram, Jeremy; Walters, Kristen; Bulva, Jeff; Palmer, James N.; Adappa, Nithin D.; White, Andrew A.; Bosso, John V.
Abstract : Background: Aspirin‐exacerbated respiratory disease (AERD) is characterized by chronic eosinophilic rhinosinusitis, nasal polyps, asthma, and respiratory sensitivity to aspirin and nonsteroidal anti‐inflammatory drugs (NSAIDs). In addition to sensitivity to aspirin and NSAIDs, the majority of patients with AERD have been reported to have respiratory intolerance associated with the consumption of alcohol. Methods: A multicenter prospective cohort study was performed. Patients with AERD confirmed by aspirin challenge were eligible to participate. Those who described themselves as able to tolerate alcohol consumption were excluded. Patients underwent aspirin desensitization following endoscopic sinus surgery. A questionnaire was distributed to patients before and after desensitization to determine pre‐desensitization and post‐desensitization symptoms associated with alcohol ingestion. Results: Forty‐five patients were enrolled and 37 patients completed the study. The most common pre‐desensitization symptoms were nasal congestion (95.6%), rhinorrhea (46.7%), and wheezing (40%). Improvement in the ability to tolerate alcohol was noted in 86.5% of participants (95% confidence interval [CI], 75.5% to 97.5%) and 70.3% of participants (95% CI, 55.5% to 85.0%) described desensitization to be "very helpful" or "extremely helpful" for their ability to tolerate alcohol. Conclusion: The majority of patients with AERD who experience respiratory symptoms with alcohol consumption describe improvement in this domain following aspirin desensitization.